Synthesis of Some Heterocyclic Compounds Via Cyclization of Imidoyl Chloride - G. T. Sedeek (College of Education for Pure Sciences, 2013)
Abstract Some substituted pyrazoline 3(a-e) were prepared from the reaction of acrelonitril with some substituted imidoyl chloride 2(a-e) (which prepared from substituted - N - phenyl hydrazide 1(a-e) on treatment with phosphorous penta chloride). Compounds 3(a-e) were then transformed into the corresponding imidate hydrochloride 4(a-e) during the reaction with hydrochloric acid in absolute ethanol. Compounds 4(a-e) were allowed to react with either p - nitro phenyl hydrazide, sodium azid or ethylene diamine giving the corresponding 1,2,3 - substituted triazoles 5(a-e), 1,2,3,4- substituted tetrazoles 6(d,e) and imidazoles 7(d,e) respectively.